Pengaruh Aplikasi Rencana Kegiatan Anggaran Sekolah (ARKAS) Dan Aplikasi Sistem Informasi Manajemen Bos Terhadap Akuntabilitas Pelaporan Keuangan Dana Bos di Kota Makassar - Lestari Wahyuni; Mursalim Mursalim; Andi Nurwana (Journal on Education, 2023)
This study aims to empirically prove the Effect of the School Budget Activity Plan Application (ARKAS) and the BOS Management Information System Application on Financial Reporting Accountability in Makassar City. The analytical tool used in this research is using multiple linear statistical tests and questionnaires as research instruments. The population in this study was 78 respondents using the census method.The results of this study prove that the first hypothesis which states that the Application of the School Budget Activity Plan (ARKAS) has an effect on Financial Reporting Accountability is acceptable and significant at α = 0.01. The second hypothesis which states that the BOS Management Information System Application affects the Accountability of Financial Statements is accepted and significant at α = 0.001.